(untitled) (Global Journal of Management and Business Research, 2018)
Summary: The paper objective is to measure the sensitivity of operational risk to the return on financial assets in Cameroon. The importance of bankruptcies and banking transactions observed over the last 20 years between the monetary authorities on the failures. Our sample consists of individual data from four banks in Cameroon. The data on the explanatory variables will be extracted from various bank numbers of banks and financing institutions, as well as from COBAC. All other variables are related to financial risk indicators. They will be automatically attributed to the accounts and reports published in the official journals in Cameroon. Our analysis shows that operational risk factors have a significant influence on the performance of banks’ assets in Cameroon.